India's Rise as an Asian Power : Nation, Neighborhood, and Region - Gordon, A. D. D. (Book collections on Project MUSE., 2014)
India's Rise as an Asian Power examines India's rise to power and the obstacles it faces in the context of domestic governance and security, relationships and security issues with its South Asian neighbors, and international relations in the wider Asian region. Instead of a straight-line projection based on traditional measures of power such as population size, economic growth rates, and military spending, Sandy Gordon's nuanced view of India's rise focuses on the need of any rising power to develop the means to deal with challenges in its domestic, neighborhood (South Asia), and regional (con.